2017
DOI: 10.1002/2016gl071311
|View full text |Cite
|
Sign up to set email alerts
|

Profuse activity of blue electrical discharges at the tops of thunderstorms

Abstract: Thunderstorm clouds may reach the lower stratosphere, affecting the exchange of greenhouse gases between the troposphere and stratosphere. This region of the atmosphere is difficult to access experimentally, and our knowledge of the processes taking place here is incomplete. We recently recorded color video footage of thunderstorms over the Bay of Bengal from the International Space Station. The observations show a multitude of blue, kilometer‐scale, discharges at the cloud top layer at ~18 km altitude and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 50 publications
(48 reference statements)
10
79
0
Order By: Relevance
“…The pixies and gnomes appeared atop the convective dome of the storm (Lyons et al, ). The clouds that the blue surface discharge appeared atop reached to the altitude of the tropopause or above (Chanrion et al, ). Wu et al () found that the observed NBEs were produced in vigorous convective surges of the thunderstorms and most −NBEs occurred at 14–19 km altitude between upper positive charge layer and negative screen layer at cloud top.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pixies and gnomes appeared atop the convective dome of the storm (Lyons et al, ). The clouds that the blue surface discharge appeared atop reached to the altitude of the tropopause or above (Chanrion et al, ). Wu et al () found that the observed NBEs were produced in vigorous convective surges of the thunderstorms and most −NBEs occurred at 14–19 km altitude between upper positive charge layer and negative screen layer at cloud top.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the BLEs are not identified as the pixies observed from the ground. Chanrion et al (2017) reported the observations of the blue electrical discharges recorded from the International Space Station. The blue discharges occurred at different locations on the surface of the cloud top, and they appeared isolated with a rate of~90 per min.…”
Section: 1002/2017ja024793mentioning
confidence: 99%
“…Chanrion et al () have recently described the observation of a BJ from the International Space Station. The top height of the thundercloud that initiated the BJ reached the tropopause, an atmospheric region where convection is weak.…”
Section: Introductionmentioning
confidence: 99%
“…Lyons et al () presented a series of unusual luminous events (called gnomes and pixies) atop the cloud and speculated that narrow bipolar events (NBEs) might be connected to them. Chanrion et al () presented a new view of blue jets on the top of thunderstorms from the International Space Station, but the recorded images could not infer the altitude where the observed blue jet originated. Edens () reported the detection of downward negative breakdown from the screening charge layer into the upper positive charge region by the Lightning Mapping Array (LMA), and the corresponding upward positive breakdown was detected photographically as blue starter emanating from the cloud top, indicating that it occurred between the upper positive charge region and the inferred negative screening charge region.…”
Section: Introductionmentioning
confidence: 99%